TÚRKIY TIL BILIMINDE FEYILDIŃ DÁREJE KATEGORIYASÍNÍŃ ÚYRENILIWI - Qudaybergenov, M.S.; Reymova, G.J. (SCIENCE and SOCIETY, 2026)
The article analyzes the opinions of world linguists about the category of verb voice in Turkic and Karakalpak linguistics. It was emphasized that the in-depth study of the verb voice category has become one of the most pressing issues under consideration as a subject of scientific research.